STRATEGI HUMAS YAYASAN ASH-SHOMAD INTERNASIONAL DALAM MEMBENTUK CITRA YAYASAN MELALUI KEGIATAN YAQOWIYU DI KECAMATAN JATINOM KABUPATEN KLATEN - Bonfilio Dedo; Sofia Ningsih Rahayu Putri; Rahmat Wisudawanto (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2023)
Public relations has an important role and function in the institution's development. This role demands the development of good relations with the public. Public relations must also have a strategy in carrying out their duties. Therefore, public relations strategies and tasks must be planned. This study aims to determine the implementation of the public relations strategy of the Ash-Shomad International Foundation in forming the foundation's image through Yaqowiyu activities. This study used the descriptive qualitative method. The data collection method was carried out by observation and interviews with the public relations of the Ash-Shomad International Foundation and the people involved in Yaqowiyu activities. The results of this study indicate that the public relations strategy applied by the Ash-Shomad International Foundation in Yaqowiyu activities can form a positive image in the community. Keywords: Strategy, Public Relations, Image, SWOT Analysis